Learning Management System (LMS) pada E-Learning Menggunakan Metode Agile dan Waterfall berbasis Website - Alfath Yauma; Iskandar Fitri; Sari Ningsih (KITA Institute, 2021)
The education information delivery system at the MA Alwutsqo school is still being carried out as usual even though the pandemic outbreak in Indonesia is still not over. Because the school does not have a system to support distance learning. By implementing health protocols and teaching and learning time events, students often do not get an understanding of the material presented by the teacher. Learning Management System (LMS) is one of the systems needed by the school. Therefore, the authors designed a website-based E-learning application system with the aim of helping the learning and teaching process at MA Alwutsqo Depok City. The design of this information system uses waterfalls and system development is carried out using the Agile method. The result is that students can download the material that has been delivered and can do the exercises given by the teacher without recommendations by time and space.Keywords:E-learning, Webite, Metode Waterfall, Metode Agile, Learning Management System (LMS).